2016
DOI: 10.1016/j.fgb.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The circadian system as an organizer of metabolism

Abstract: The regulation of metabolism by circadian systems is believed to be a key reason for the extensive representation of circadian rhythms within the tree of life. Despite this, surprisingly little work has focused on the link between metabolism and the clock in Neurospora, a key model system in circadian research. The analysis that has been performed has focused on the unidirectional control from the clock to metabolism and largely ignored the feedback from metabolism on the clock. Recent efforts to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 52 publications
(75 reference statements)
1
23
0
Order By: Relevance
“…Crosstalk between gene regulation in response to different nutritional conditions and the light response pathway is extensive (Schmoll, 2018; Stappler et al, 2017) and was also shown in N. crassa (Sancar et al, 2012; Schmoll et al, 2012). FREQUENCY (FRQ; NCU02265) is a key component of the Neurospora circadian clock, allowing precise daily control of several processes, including metabolism (Hurley et al, 2016; Montenegro-Montero et al, 2015). Under day-night regimes, FRQ is known to be subjected to extensive phosphorylations (> 75 unambiguous S/T sites) throughout its daily cycle, many of which are key in determining the proper pace of the clock (Baker et al, 2009; Larrondo et al, 2015; Tang et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crosstalk between gene regulation in response to different nutritional conditions and the light response pathway is extensive (Schmoll, 2018; Stappler et al, 2017) and was also shown in N. crassa (Sancar et al, 2012; Schmoll et al, 2012). FREQUENCY (FRQ; NCU02265) is a key component of the Neurospora circadian clock, allowing precise daily control of several processes, including metabolism (Hurley et al, 2016; Montenegro-Montero et al, 2015). Under day-night regimes, FRQ is known to be subjected to extensive phosphorylations (> 75 unambiguous S/T sites) throughout its daily cycle, many of which are key in determining the proper pace of the clock (Baker et al, 2009; Larrondo et al, 2015; Tang et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Reversible modifications in protein phosphorylation mediated by protein kinases or phosphatases represents a mechanism that is frequently employed by eukaryotic cells to transmit environmental cues and initiate signal transduction pathways, such as for transcription factor activation (Whitmarsh and Davis, 2000), cellular localization, protein stability, protein-protein interactions, DNA binding, and enzymatic activity (Breitkreutz et al, 2010; Pawson, 2007). Most cellular processes are in fact regulated by the reversible phosphorylation of proteins on serine (S), threonine (T), and tyrosine residues (Y) (Ficarro et al, 2002; Wart and Unit, 1993), including metabolism, movement, the circadian rhythms and many other (Cohen, 2000; Hurley et al, 2016; Wart and Unit, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Among these adaptation mechanisms the most intensively investigated process is temperature compensation. Although a tight interaction between metabolism and the circadian clock has been shown at almost all levels of organisms (1)(2)(3), it is still poorly understood how molecular timekeeping is compensated against changes in nutrient availability. Neurospora crassa belongs to the most extensively examined model systems in the field of circadian research and has proved to serve as a useful tool for the investigation of different aspects of circadian regulation including metabolic compensation of the circadian clock (4).…”
Section: Introductionmentioning
confidence: 99%
“…2016), including consciousness and sleep (C irelli 2009), feeding and metabolism (X u et al . 2008; H urley et al . 2016), learning and memory (X u et al .…”
Section: Introductionmentioning
confidence: 99%
“…Circadian clocks are biochemical pathways characterized by cyclical protein expression. They play a critical role in a wide variety of behavioral and physiological processes, and a better understanding of their genetic and biochemical bases could advance research in many areas (P reussner and H eyd 2016; S harma et al 2016), including consciousness and sleep (C irelli 2009), feeding and metabolism (X u et al 2008; H urley et al 2016), learning and memory (X u et al 2008; C houhan et al 2015), stress and immunity (D umbell et al 2016), inflammation (C arter et al 2016), cancer (S ephton and S piegel 2003; M asri et al 2015; S alavaty 2015; M olina -R odrĂ­guez and Á lvarez 2016), and psychological functioning (M c C lung 2013; P arekh et al 2015; C oogan et al 2016).…”
Section: Introductionmentioning
confidence: 99%